Optimal design of raising retirement age - Zhang, Jinggong (2024)
Population aging threatens the future fiscal balance of the public pension system across many countries, and policymakers have often undertaken parametric pension reform as a solution. However, any reform will inevitably introduce intergenerational conflicts and thus needs a gradual transition to allow individuals to slowly adapt to their new retirement plans. In this article, we study the optimal schedule for lifting the full retirement age using the optimal control approach. Given the aggregate actuarial loss of the pension system, our target is to smoothly distribute the deficit across different generations, subject to a fairness constraint that prohibits any cohorts from taking advantage of others. We further illustrate our results using China as an empirical example and investigate the impacts of different actuarial assumptions, benefit accrual formulae, and population structures.